Structural observations and biomechanical measurements of clarinet reeds made from Arundo donax. Issue 8 (9th May 2017) - Kawasaki, Masahiro; Nobuchi, Tadashi; Nakafushi, Yuta; Nose, Masateru; Shibata, Masateru; Li, Peng; Shiojiri, Makoto
Abstract: Plant anatomy was examined for two clarinet reeds made out of Arundo donax by different means of microscopy: light microscopy, low‐energy secondary electron scanning electron microscopy (SEM), backscattered electron SEM, and helium ion microscopy (HiM). The local indentation hardness H IT and Young's modulus E IT of different tissues on their cross sections were measured. A vascular bundle (Vb) ( H IT  = 60–100 MPa, E IT  = 1, 500–2, 000 MPa) that includes soft tissues of phloem and xylem and a vascular bundle sheath (Bs) ( H IT  = 300–500 MPa, E IT  = ∼7, 000 MPa) form a pipe of the strong string along the longitudinal direction of the cane. This Vb/Bs string is connected transversally with a net of thin cell‐walls of parenchyma cells (Pa) ( H IT  = 70–200 MPa, E IT  = 2, 000–3, 000 MPa) that also range along the longitudinal direction of the cane. It was turned out that the acoustic quality of a reed is mainly ascribed to the shape and configuration of Vb and the size of Pa. A reed where Vb bundles with continuous Bs rings are homogeneously distributed with higher proportion among a softer network of small Pa cells enables musical performance. Abstract : Plant anatomy was examined for two clarinet reeds made out of Arundo donax by different means of microscopy, and local indentation hardness of different tissues was measured to understand the acoustic quality relationship to the structure.